IFNγ directly counteracts imatinib-induced apoptosis of primary human CD34+ CML stem/progenitor cells potentially through the upregulation of multiple key survival factors. (31st December 2022) - Ujvari, Dorina; Malyukova, Alena; Zovko, Ana; Yektaei-Karin, Elham; Madapura, Harsha S; Keszei, Marton; Nagy, Noemi; Lotfi, Kourosh; Björn, Niclas; Wallvik, Jonas; Stenke, Leif; Salamon, Daniel
ABSTRACT: Tyrosine kinase inhibitors (TKIs) have dramatically improved the survival in chronic myeloid leukemia (CML), but residual disease typically persists even after prolonged treatment. Several lines of evidence suggest that TKIs administered to CML patients upregulate interferon γ (IFNγ) production, which may counteract the anti-tumorigenic effects of the therapy. We now show that activated T cell-conditioned medium (TCM) enhanced proliferation and counteracted imatinib-induced apoptosis of CML cells, and addition of a neutralizing anti-IFNγ antibody at least partially inhibited the anti-apoptotic effect. Likewise, recombinant IFNγ also reduced imatinib-induced apoptosis of CML cells. This anti-apoptotic effect of IFNγ was independent of alternative IFNγ signaling pathways, but could be notably diminished by STAT1-knockdown. Furthermore, IFNγ upregulated the expression of several anti-apoptotic proteins, including MCL1, PARP9, and PARP14, both in untreated and imatinib-treated primary human CD34+ CML stem/progenitor cells. Our results suggest that activated T cells in imatinib-treated CML patients can directly rescue CML cells from imatinib-induced apoptosis at least partially through the secretion of IFNγ, which exerts a rapid, STAT1-dependent anti-apoptotic effect potentially through the simultaneous upregulation of several key hematopoietic survival factors. These mechanisms may have a major clinical impact, when targeting residual leukemic stem/progenitor cells in CML.